2009
DOI: 10.1590/s0104-11692009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding knowledge and practice of health professionals in public health care services

Abstract: CONOCIMIENTOS Y PRÁCTICAS DE PROFESIONALES DE LA SALUD SOBRE AMAMANTAMIENTO MATERNO EN SERVICIOS PÚBLICOS DE SALUD CONHECIMENTOS E PRÁTICAS DE PROFISSIONAIS DE SAÚDE SOBRE ALEITAMENTO MATERNO EM SERVIÇOS PÚBLICOS DE SAÚDE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
2
13
0
5
Order By: Relevance
“…The results are in accordance with a previous study, in which health professionals' advice regarding breastfeeding problems has been thought to be inadequate (Izatt, 1997). The present study confirms that there is an urgent need for physicians and nurses to learn more knowledge about breastfeeding, and to improve their education to enable them to promote breastfeeding (Izatt, 1997; Silvestre et al ., 2009).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results are in accordance with a previous study, in which health professionals' advice regarding breastfeeding problems has been thought to be inadequate (Izatt, 1997). The present study confirms that there is an urgent need for physicians and nurses to learn more knowledge about breastfeeding, and to improve their education to enable them to promote breastfeeding (Izatt, 1997; Silvestre et al ., 2009).…”
Section: Discussionsupporting
confidence: 83%
“…In the USA, many women have reported that they do not receive positive breastfeeding messages from medical staff (DiGirolamo et al ., 2003). Moreover, several studies have reported that both obstetrician–gynecologists and pediatricians lack confidence in their skills to support breastfeeding, do not have adequate training in breastfeeding management, and are skeptical of the benefits of breastfeeding over formula (Schanler et al ., 1999; Silvestre et al ., 2009). Although health professionals can positively influence breastfeeding women through providing effective support, they can also be a negative source of support when they provide women with inaccurate and/or inadequate breastfeeding information and recommendations (Humenick et al ., 1998; Dykes, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caldeira et al 21 (2007) Cross-sectional descriptive IV Physicians show that they still have little scientific support to address more complex issues and fail to offer adequate support to mothers with greater difficulties in breastfeeding. Silvestre et al 22 (2009) Qualitative descriptive IV Mothers report that they do not receive enough support to breastfeed, or assign blame to a professional, instead of themselves. Gökçay et al 23 (1997) Qualitative descriptive IV Breastfeeding practices are the result of hospital dynamics, which also includes the health team attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Esse percentual se iguala ao de países em desenvolvimento e chega bem próximo ao de países menos desenvolvidos, que apresentam prevalência de 37% (2) . Diante disso, os índices de AM, principalmente o exclusivo, ainda são baixos, o que pode ser explicado por alguns determinantes que interferem nessa prática, como a escolaridade materna, a efetividade da licença maternidade, a aplicação dos programas e políticas que visam a expansão da amamentação e o apoio exercido pelos profissionais de saúde e pela rede social que envolve essa mulher (1,(3)(4)(5) . Entre estes, destaca-se também a autoeficácia materna em amamentar, que pode influenciar no início e na manutenção do AM.…”
Section: Introductionunclassified